Controlled growth of large-scale uniform 1T′ MoTe2 crystals with tunable thickness and their photodetector applications. Issue 6 (6th April 2020) - Wang, Xiaojian; Shang, Jing; Zhu, Meijie; Zhou, Xi; Hao, Rui; Sun, Lina; Xu, Hua; Zheng, Jianbang; Lei, Xingfeng; Li, Chun; Kou, Liangzhi; Feng, Qingliang
Abstract : Large-scale uniform MoTe2 crystals with a wide range of photo-response from 532 nm to 1550 nm are controllably grown by a molecular sieve-assisted method. Abstract : The monoclinic-phase 1T′ MoTe2 crystal exhibits inversion symmetry as an anisotropic semi-metal, dictating its interesting quantum transport phenomenon and other novel physical properties. However, large-scale controllable growth of uniform MoTe2 crystals still remains a great challenge, hindering its further fundamental research and applications for novel devices. Herein, we report a modified growth method for synthesizing few-layer 1T′ MoTe2 crystals with large-scale uniformity with the assistance of molecular sieves. The theoretical simulations demonstrated that due to the temperature-dependent formation energies of different edges, the edge of (010) orientation shows a higher thermodynamic stability than that of (100) orientation, and results in the anisotropic growth behavior of 1T′ MoTe2 crystals while the temperature changes. The photoresponse of tri-layer 1T′ MoTe2 -based devices shows a broad-spectrum response from 532 nm to 1550 nm. The photo-response time of 1T′ MoTe2 crystals demonstrates that it supposes to be the synergistic mechanism of photo-conductive and photo-radiation effects. Our findings not only provide a method for the controllable growth of anisotropic two-dimensional materials at a wafer scale, but also explore a broad-spectrum photodetector with the MoTe2 -based device.